Binocular rivalry and emotion: Implications for neural correlates of consciousness and emotional biases in conscious perception. (November 2019) - Hernández-Lorca, María; Sandberg, Kristian; Kessel, Dominique; Fernández-Folgueiras, Uxía; Overgaard, Morten; Carretié, Luis
Abstract: Studies of the neural correlates of consciousness (NCCs) combining MEG/EEG with behavioral data have described two main time ranges relating to conscious perception: 130–320 (the visual awareness negativity; VAN) and 300–500 (P3a) ms after stimulus onset. At the same time, two event-related potential (ERP) peaks have shown an emotional modulation of endogenous attention: the early posterior negativity (EPN; peaking around 250 msec) and the late positive potential (LPP, peaking around 600 msec). Furthermore, an emotional bias on conscious perception has been reported in Binocular Rivalry (BR) studies. Here, we combined an intermittent BR paradigm with neutral and emotional stimuli while recording the behavioral subjective perception and ERPs with two aims: i) to explore the NCCs of emotional content in the time ranges previously described, and ii) to study the emotional bias in conscious perception as first percept when neutral and emotional images rival against each other. First, results revealed a specific ERP emotional modulation (emotional content awareness modulation; ECAM) at the VAN time range. This was the first time window sensitive to the emotional information and showing the strongest modulation in conscious emotional content. Second, results revealed an emotional bias in conscious perception towards the positive valence. This work shows how conscious perception pertaining to emotional content relates to perceptual areas at the VAN latency, which supports the claim of the 130–320 msec time window as the earliest NCC and extends the claim to apply to more than visual perceptual features. Additionally, our findings show that positive and negative content modulates the conscious perception differently.